Pengembangan Conceptual Design Pengelolaan Air di Perkebunan Kelapa Sawit: (Studi Kasus PT XYZ Kalimantan Timur) - Kusuma, Susandi; Hermantoro Hermantoro; Krisdiarto, Andreas Wahyu; Gilang Arya Dipayana; Erik Febriarta; Owen Max (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
Oil palm is a leading commodity that makes a major contribution to Indonesia’s economy, yet a significant productivity gap remains between actual and potential yields. A principal cause is suboptimal water management, which leads to flooding during the rainy season and drought in the dry season. This study develops a Conceptual Design (CD) for water management to map existing problems, analyse root causes, formulate improvement measures, and present a macro-level cost estimate for the study site. The research was conducted at an oil palm plantation in East Kalimantan anonymized as “PT XYZ.” The site was selected due to recurrent flooding and a recent change in ownership that limited data availability, making it well-suited for a CD-stage assessment. The objective is to identify water management issues and propose effective recommendations. A quantitative approach integrates primary data from field observations and measurements with secondary data. The analyses cover flood problem assessment, Water Management Zoning (WMZ/ZPA), rainfall analysis, hydrology, hydraulics, improvement proposals, and macro cost estimation. Results indicate that challenges are driven by swampy land conditions and inadequate channel and hydraulic structure capacity. Micro-watershed delineation using DEMNAS identified four ZPAs totalling 479–4,061 ha. Design rainfall was derived from CHIRPS satellite data using a log-normal distribution. Hydrologically, peak discharges range from 3.87–22.58 m³/s for the 2-year return period and 4.46–26.31 m³/s for the 5-year return period. Hydraulically, the proposed dimensions for rivers, outlet drains, carrier drains, and field-edge drains are 4×3×2 m to 9×7×3 m (T=2 years) and 4×3×2 m to 10×8×3 m (T=5 years), while collection and main drains are proposed at 3×2×2 m for both return periods. The total estimated investment for the 5-year design scenario is IDR 27,999,263,000.